﻿Three new species of the spider genus Liphistius (Araneae, Mesothelae, Liphistiidae) from Thailand - Yi Zhan; Varat Sivayyapram; Fengxiang Liu; Daiqin Li; Xin Xu (ZooKeys, 2022)
We diagnose and describe three new species of the primitively segmented spider genus Liphistius from Thailand, based on male palp and female genital morphology: L. hatyai Zhan & Xu, sp. nov. (♂♀), L. keeratikiati Zhan & Xu, sp. nov. (♂♀), and L. inthanon Zhan & Xu, sp. nov. (♂♀). The classification of the three new species of Liphistius is discussed: L. hatyai sp. nov. and L. keeratikiati sp. nov. are assigned to the trang-group, and L. inthanon sp. nov. is placed in the bristowei-group according to male palp and female genital morphology.